KINEMATIC DESIGN AS A MEANS OF SPECIFICATION OF AIRCRAFT COORDINATES - AFTANAZIV, IVAN; SHEVCHUK, LILIA; STROHAN, ORYCA; KORENDIY, VITALIY; STRUTYNSKA, LESYA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
In the article, it is proposed to use the mathematical apparatus of kinematic design in the processes of specifying the coordinates of aircraft. The proposed scheme of the spatial arrangement of a group of unmanned kamikaze drones, aimed at detecting and eliminating enemy reconnaissance and attack unmanned aerial vehicles. Mathematical dependencies are proposed for the first time, which allow a drone operator equipped with artificial intelligence programs (the conditional leader of a group of interceptor drones) to alternately direct the liquidator drones located closest to them in the airspace to eliminate enemy drones. The schematic diagram of the use of kinematic design for the elimination of enemy unmanned aerial vehicles demonstrates the mechanism for optimizing the sequence of attacks by liquidator drones on enemy objects. The sequence of actions and calculations and comparative analysis is illustrated on the proposed typical block diagram of the involvement of artificial intelligence and kinematic design mechanisms for the elimination of enemy subversive unmanned aerial vehicles. The possibilities and advantages of the proposed method of determining the coordinates of enemy aircraft are illustrated on the example of a group (so-called "swarm") of liquidator drones, led by a drone-operator, with specific numerical values ​​of the parameters of their spatial movements and variable coordinates. The main of these advantages is a higher percentage of the probability and accuracy of determining the coordinates of enemy aircraft, and therefore, their possible elimination.